HUBUNGAN KUALITAS PELAYANAN KESEHATAN TERHADAT TINGKAT KEPUASAN KLIEN DI RUANG RAWAT INAP DI RS TANI DAN NELAYAN KABUPATEN BOALEMO - Euis Hidayat; Rini Asnawati (program studi ilmu keperawatan fakultas ilmu kesehatan universitas muhammadiyah gorontalo, 2021)
The objective of this research is to find out the correlation of health service quality on client’s satisfaction in medical ward at RSTN Kab. Boalemo. This research used descriptive analytics design with cross sectional. The samples are 65 respondents, collecting samples used random sampling technique with chi square statistical test analysis with significant level a (0,05). The research result of five dimensions in health service quality on client’s satisfaction level showed p value of reliability 0,00, guarantee 0,02, conclusive evidence 0,01, empathy 0,01 and responsiveness 0,00. It’s concluded that from five dimensions of health service quality has the correlation on client’s satisfaction level in medical ward of RSTN kab. Boalemo. Every health service must be noticed and give the professional service to increase the quality of service.